Adalimumab biosimilar ABP 501 is equally effective and safe in long-term management of inflammatory bowel diseases patients when used as first biologic treatment or as replace of the ADA originator for a non-medical reason - Mocci, Giammarco; Cingolani, Arianna; Orrù, Giorgia; Felice, Carla; Onidi, Francesca Maria; Lombardi, Gianmarco; Checchin, Davide; Colucci, Raffaele; Grossi, Laurino; Ferronato, Antonio; Rocchi, Chiara; Ascolani, Marta; et al. (Frontiers in Gastroenterology, 2023)
Objective Biosimilars represent a new opportunity for inflammatory bowel disease (IBD) treatment and economic sustainability of therapies. This study aimed to evaluate the efficacy and long-term safety of the adalimumab biosimilar ABP 501 in biologic-naïve vs. biologic-switched IBD patients. Methods A retrospective observational study was conducted using a database of patients with IBD treated with ABP 501, biologic-naïve or switched from the original, at eight IBD centers. We included adult patients with at least one year of follow-up. The primary objective of this study was to assess the efficacy (persistence) and safety (adverse event rate) of ABP 501 therapy. Results A total of 118 patients with IBD were included in the analysis: 84 patients with Crohn’s disease (CD) (39 women, 45 men, mean age 40.4 ± 14.3 years; 33% biologic-naïve) and 34 patients with ulcerative Colitis (UC) (16 women, 18 men, mean age 38.9 ± 14.9 years; 61.8% biologic-naïve). Regarding the primary endpoint, no difference was observed in the efficacy between biologic-naïve patients and patients with Adalimumab (ADA) originator replacement for non-medical reasons in terms of long-term persistence. However, ABP 501 showed a higher percentage of sustained clinical remission at 2 years in patients with CD (64 patients, 77%) than in those with UC (15 patients, 45.5%; p=0.00091). Nine patients (six with CD and three with UC) experienced adverse events that led to drug discontinuation in three. Conclusions APB 501 showed a good safety and efficacy profile in maintaining clinical response at 2 years in patients with IBD, both as a treatment-naïve and as a replacement for ADA originator for non-medical reasons.